Det stillasittande, överviktiga och kostsamma barnet: En kritisk analys av hur WHO och OECD konstruerar barns fysiska aktivitet inom utbildning - Johansson, Jonas (Educare, 2025)
Physical activity among children has been a topical subject in social debate in recent years. The Swedish school-system is governed by policy, shaped by negotiations between different actors as politicians, public authorities, researchers and persons active in education. These actors are most probably influenced by different social forces that in turn convey varying knowledge, norms and values. This paper focuses on international actors who seek to influence the content of education policy. The aim is to investigate how children and their physical activity are constructed in official documents produced by WHO and OECD. Two documents were analyzed with inspiration from critical discourse analysis. The result shows that children are constructed as sedentary, overweight and costly, and that the problem should be solved within education by regulated physical activity. The analysis highlights a public health discourse and a neoliberal market discourse. Within these discourses, natural scientific and sporting knowledge, norms and values are recontextualized, mostly for economic gain. This might lead to a rather instrumental view on children and a reorganization of education. In the discussion it is argued for a possible discourse of democracy and that concepts such as influence and participation are given a prominent position in educational policy.